Pengaruh Promosi Digital Tiktok dan Lokasi terhadap Keputusan Pembelian Pelanggan Salapak Micro Shop di Kota Bandung - Trian Permana Putra; Rizka Aula Assaf (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
This study addresses the issue of unstable sales performance at Salapak Micro Shop in Bandung City, even though digital promotion through TikTok has been implemented and the business location has been relocated. These conditions indicate the need to identify key factors influencing customer purchasing decisions. The purpose of this research is to examine the effect of TikTok-based digital promotion and business location on customers’ purchasing decisions, both partially and simultaneously. The study employs an explanatory research design with a quantitative approach. Data were collected through questionnaires distributed to 95 customers who had made purchases at Salapak Micro Shop and were exposed to TikTok promotional content. The sampling technique used was purposive sampling, and the data were analyzed using multiple linear regression with SPSS version 27. The findings reveal that TikTok digital promotion has a positive and significant effect on purchasing decisions. Business location also shows a positive and significant influence on purchasing decisions. Simultaneously, digital promotion through TikTok and business location significantly affect customers’ purchasing decisions. The coefficient of determination indicates that both variables contribute substantially to purchasing decisions, while the remaining variance is influenced by other factors not examined in this study. These results highlight the importance of integrating effective digital promotion strategies with strategic location management to strengthen the competitiveness of UMKM retail businesses.